Analysis of Consumer Perceptions of Healthy Snacks - Vivian, Vivian; Aripradono, Heru Wijayanto (Almana : Jurnal Manajemen dan Bisnis, 2025)
Healthy snacks are often one of the forgotten options for some people, with the mindset “Healthy snacks are not tasty, healthy snacks are tasteless.” However, not all healthy snacks are bland, it's more about the food we eat with the original or natural flavour of the food itself and no MSG added to the food. As awareness about the importance of healthy eating increases, there is a need to change consumer perceptions that healthy snacks are also delicious. Besides, there are some consumers who are confused to find healthy yet tasty snacks. In this case, an analysis of consumer perception for healthy snacks in Batam city will be conducted. This research will use qualitative methods in the form of interview, observation and the design thinking approach. The design thinking approach includes the stages of empathize, define, ideate, prototype and test to understand consumer needs and formulate problems. With this method, it is expected to create solutions to consumer perception for healthy snacks and provide one example of a healthy snack product idea.